2017
DOI: 10.5506/aphyspolb.48.1411
|View full text |Cite
|
Sign up to set email alerts
|

Non-classical Behavior of Moving Relativistic Unstable Particles

Abstract: We study the survival probability of moving relativistic unstable particles with definite momentum p = 0. The amplitude of the survival probability of these particles is calculated using its integral representation. We found decay curves of such particles for the quantum mechanical models considered. These model studies show that late time deviations of the survival probability of these particles from the exponential form of the decay law, that is the transition times region between exponential and non-exponen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(51 citation statements)
references
References 30 publications
1
50
0
Order By: Relevance
“…In summary, we have described the transformation of times in the decay laws of moving unstable quantum systems, which are induced by the change of reference frame, via relations (33)-(35), and we have found that, under determined conditions, the relativistic dilation of times, Eqs. (36) and (37), holds, approximately, over the time window (26), in the laboratory reference frame, and over the time window (38), in rest reference frame. These descriptions and properties constitute the last of the two main results of the paper.…”
Section: Transformation Of Intermediate Times and Relativistic Time Dmentioning
confidence: 94%
See 2 more Smart Citations
“…In summary, we have described the transformation of times in the decay laws of moving unstable quantum systems, which are induced by the change of reference frame, via relations (33)-(35), and we have found that, under determined conditions, the relativistic dilation of times, Eqs. (36) and (37), holds, approximately, over the time window (26), in the laboratory reference frame, and over the time window (38), in rest reference frame. These descriptions and properties constitute the last of the two main results of the paper.…”
Section: Transformation Of Intermediate Times and Relativistic Time Dmentioning
confidence: 94%
“…For the sake of clarity, we describe below the decay laws in the laboratory frame S p , where the unstable system moves with constant linear momentum p, by following Ref. [36]. Let H be the Hilbert space of the quantum states of the unstable system.…”
Section: Moving Unstable Quantum Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The description is performed by following Ref. [16]. Let the state kets |m, p belong to the Hilbert space H of the quantum states of the unstable system and be the common eigenstates of the linear momentum P and of the Hamiltonian H self-adjoint operator.…”
Section: Moving Unstable Quantum Systems and Oscillating Decay Ratementioning
confidence: 99%
“…In the present notation, 0, m| and p, m| are the bras of the state kets |m, 0 and |m, p , respectively. In the rest reference frame of the unstable system the survival amplitude reads A 0 (t) = φ|e −ıHt |φ , where ı is the imaginary unit, and is given by the following integral expression [8,7,11,12,10],…”
Section: Moving Single-mass Unstable Quantum Systemsmentioning
confidence: 99%